Directional interference suppression using a spatial relative transfer function feature - Braun, Sebastian; Tashev, Ivan (International Conference on Acoustics, Speech and Signal Processing, 2019)
Many speech enhancement systems consist of a beamformer and a spectral suppression postfilter. While it is well understood how to design beamformers to suppress either non-directional or directional interference, their suppression ability is limited by the number, type and positions of microphones. However, spectral postfilters that can further increase the suppression, are usually only designed to suppress non-directional noise. In this work, we propose a spatially selective spectral suppressor addressing directional and non-directional interference. The proposed suppressor is based on the relative transfer function of the target source location. While existing directional suppression techniques are limited to farfield scenarios or certain microphone geometries, we propose a general approach without restrictions on the microphone array and without farfield assumption. We show that the proposed spatial suppressor is able to suppress noise and directional interfering speakers, which substantially improves the performance of speech recognizer, and reduces undesired recognition of interfering talkers.